Pembinaan Akhlak Santri di Pondok Pesantren Darussalam Sengkubang Tahun 2023 - Nurbani; Putra, Purniadi; Sri Sunantri (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
The objective of this research is to gather information on the Moral Development Model for Santri at the Darussalam Sengkubang Islamic Boarding School in 2023. The research aims to provide a description and analysis of the method of Moral Development at the Darussalam Sengkubang Islamic Boarding School, the implementation of Moral Development at the Darussalam Sengkubang Islamic Boarding School, and the evaluation of Moral Development at the Sengkubang Islamic Boarding School. This research utilizes a qualitative approach with a descriptive design. The primary sources of data are santri supervisors and female student supervisors, while the secondary sources of data are boarding school leaders, ustadz, ustadzah, and santri residing in dormitories. Data collection techniques involve conducting semi-structured interviews with prepared and developed questions based on the relevant literature. The findings of this research indicate the model for moral development of students at the Darussalam Sengkubang Islamic Boarding School in 2023. The researcher concludes that 1) The method for fostering students' moral development at the Darussalam Sengkubang Islamic Boarding School is consistently implemented through coaching by example, guidance, habituation, and rewards. These methods are employed by ustadz, ustadzah, and male/female student dormitories during the students' tenure at the Sengkubang Darussalam Islamic Boarding School. 2) The implementation of moral development for students at the Sengkubang Darussalam Islamic Boarding School is consistently and continuously carried out by ustadz, ustadzah, and male/female boarding school supervisors. 3) The evaluation of the implementation of students' moral development at the Sengkubang Darussalam Islamic Boarding School is consistently and continuously conducted by ustadz, ustadzah, and male/female student dormitory coaches. Evaluation takes the form of daily assessments during students' participation in learning activities. Monthly evaluations are conducted based on reports compiled by ustadz, ustadzah, while the students partake in academic and Islamic boarding school programs at the Darussalam Sengkubang Islamic Boarding School.